New Diabetic Medication Sodium-Glucose Cotransporter-2 Inhibitors Can Induce Euglycemic Ketoacidosis and Mimic Surgical Diseases: A Case Report and Review of Literature - Kietaibl, Antonia-Therese; Fasching, Peter; Glaser, Karl; Petter-Puchner, Alexander H. (Frontiers in Surgery, 2022)
Background: Euglycemic diabetic ketoacidosis (EDKA) is a potentially life-threatening condition and reported side effect of antidiabetic sodium-glucose-cotransporter-2-inhibitors (SGLT2-I). The analysis of the herein presented case and its management formed the incentive to prepare this multidisciplinary work and includes an overview about perioperative SGLT2-I induced ketoacidosis. Method: A PubMed search on relevant entries was conducted combining the terms ‘euglycemic diabetic ketoacidosis’ AND ‘surgery’. Results: A total of 33 articles on SGLT2-I induced ketoacidosis in the context of surgical treatment were identified. According to this literature research risk factors for the development are infection, perioperative fasting, surgical stress and insulin dose reduction. Conclusion: Unspecific symptoms, mimicking acute abdomen and normoglycemia can lead to delayed diagnosis of EDKA and might harm patients under SGLT2-I therapy in the perioperative setting. SGLT2-I medication should be withheld for at least 24-48 hours prior to surgery according to this review of literature and restarted only in stable clinical conditions to avoid the severe complication of EDKA.